ASSET DIVERSIFICATION THROUGH APPLICATION HOARDING INVESTMENTS: Array - Verbytska, V.; Bredikhin, V. (Municipal economy of cities. Series: «Economy science», 2020)
The current state and tendencies of development of hoarding investment by legal entities and the population of the country are considered in the article. It is especially important that these investments are available not only for legal entities, but also for the population, where there is a clear relationship between changes in the share of savings hoarded by private individuals and fluctuations in uncertainty, and growing investment and hoarding demand are the consequences of the financial crisis. inflation expectations, geopolitical instability and growing needs for diversification. On the basis of economic-theoretical analysis the essence, character of behavior, types and conditions of realization of hoarding investments (TI) in crisis economy are analyzed. The concept of "hoarding investments" has been clarified. The main subjects and objects of hoarding investments are identified. The objects of hoarding investments are bank metals (and coins from them) precious stones, jewelry, art objects and antiques. Available types, modern tendencies, methods and conditions of realization of hoarding investments are investigated. Coins issued by both Ukrainian and foreign banks were found to be numismatically valuable. However, foreign coins entering our market are usually issued in large numbers and, accordingly, have less numismatic value. In the United States, consumption of diamond jewelry is constantly growing due to the combination of domestic market unsaturation with well-established lending mechanisms, Europe is characterized by stagnation in the consumption of diamond jewelry, and for some countries, such as Germany, even a reduction. Hoarding investments in collectibles are specific in nature, due to their complexity, the relatively narrow market for each type of collection, the need for special knowledge and skills for proper investment.